How does data-driven supply chain analytics capability enhance supply chain agility in the digital era? - Cui, Li; Wang, Ziyi; Liu, Yang; Cao, Guikun (International journal of production economics, 2024)
Supply chain analytics capability has recently gained more attention from both scholars and practitioners. Through the lens of information processing theory, this study examined how supply chain analytics capability impacts supply chain agility in the digital era with the associated adoption of digital technologies and platforms by companies. To obtain relevant data, a large-scale survey of Chinese manufacturing firms was conducted. Supply chain integration capability was evaluated as mediator and digital platform was evaluated as moderator. The results show that supply chain integration capability can mediate the effect of supply chain analytics capability on supply chain agility; moreover, supply chain analytics capability has a stronger impact on supply chain agility under a high level of digital platform adoption. These findings deepen the understanding of the role of supply chain analytics capability in supply chain management. This paper also provides managerial implications for enhancing supply chain agility in the digital era.